Antimicrobial mechanism of in-situ plasma activated water treatment of pathogenic Escherichia coli and Staphylococcus aureus biofilms - Binbin Xia; Heema Kumari Nilesh Vyas; Scott A. Rice; Timothy P. Newsome; Patrick J. Cullen; Anne Mai-Prochnow (Biofilm)
This study investigated the efficacy and mechanisms of inactivation against Escherichia coli UTI89 and Staphylococcus aureus NCTC8325 through an in-situ plasma-activated water (PAW) treatment. PAW was prepared by discharging atmospheric pressure cold plasma beneath the surface of sterile distilled water. The study investigated the inactivation of biofilm cells and biofilm matrix. In situ PAW treatment of both E. coli and S. aureus biofilms resulted in significant reduction in viable cells of 6.76 ± 0.01 log CFU/mL and 6.82 ± 0.02 log CFU/mL, respectively. Notably, relative to E. coli, S. aureus biofilms were rapidly inactivated by 11 min of treatment. Mechanistically, we demonstrate how PAW treatment led to significant biofilm structure disruption, inducing a significant reduction in biofilm biomass and extracellular polymer substances (EPS) matrix. We propose that disruption of the EPS, facilitated greater interaction between PAW and the bacterial cells of the treated biofilms, resulting in significant intracellular reactive oxygen and nitrogen species accumulation as well as significant membrane permeability with disruption to membrane structure resulting in rapid cell death. Collectively, these findings indicate that PAW effectively inactivates biofilms by targeting the biofilm EPS matrix and biofilm cells in both Gram-negative and Gram-positive bacteria. Whilst PAW is an emerging technology, our study underscores PAW as an effective strategy to control bacterial biofilms of both Gram-negative and Gram-positive bacteria, with utility in diverse sectors and industries. Advantageously, we highlight the multiple mechanisms of action of this technology, which possesses a capacity to overcome the challenges of antimicrobial resistance given that it targets multiple components of bacteria and their biofilms.